The Influential Factors of Teachers’ Creativity in Teaching English Language: Teacher’s Insight - Sunarti; Sonny Elfiyanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Teachers have different backgrounds, and their opinions regarding "creative teaching" or "good teaching" methods are frequently shaped by a range of elements, such as their own teaching experiences, personal incentives, and organizational limitations. This setting frames teachers' initial attempts to cultivate creative practices, and their recognition of these effects influences their subsequent level of creativity. The goal of this research is to discover the characteristics that influence English language teaching (ELT) teachers' creativity. Researchers interviewed six English as a Foreign Language (EFL) teachers to learn more about the elements that drive their passion and creativity in the classroom. Researchers discovered that teachers' motivation, technology, school support, colleagues, and teaching knowledge and experience all had an impact on their creativity. Teachers can use these five aspects as guidelines to help them incorporate creativity into their lessons. Participants also believed that their creativity was required to inspire creativity in students, make learning fun, and support their learning. The quickly evolving potential of digital environments to support student-centered and self-directed learning seems to contribute to this belief. Ultimately, this study demonstrates that teachers do not naturally possess creativity, but they may cultivate it by adopting new ideas and improving their creative teaching skills.